The Measurement of the Sensory Recovery Period in Zygoma and Blow-Out Fractures with Neurometer Current Perception Threshold - Oh, Daemyung; Yun, Taebin; Kim, Junhyung; Choi, Jaehoon; Jeong, Woonhyeok; Chu, Hojun; Lee, Soyoung (Archives of Plastic Surgery, 2016)
Background Facial hypoesthesia is one of the most troublesome complaints in the management of facial bone fractures. However, there is a lack of literature on facial sensory recovery after facial trauma. The purpose of this study was to evaluate the facial sensory recovery period for facial bone fractures using Neurometer.Methods Sixty-three patients who underwent open reduction of zygomatic and blowout fractures between December 2013 and July 2015 were included in the study. The facial sensory status of the patients was repeatedly examined preoperatively and postoperatively by Neurometer current perception threshold (CPT) until the results were normalized.Results Among the 63 subjects, 30 patients had normal Neurometer results preoperatively and postoperatively. According to fracture types, 17 patients with blowout fracture had a median recovery period of 0.25 months. Twelve patients with zygomatic fracture had a median recovery period of 1.00 month. Four patients with both fracture types had a median recovery period of 0.625 months. The median recovery period of all 33 patients was 0.25 months. There was no statistically significant difference in the sensory recovery period between types and subgroups of zygomatic and blowout fractures. In addition, there was no statistically significant difference in the sensory recovery period according to Neurometer results and the patients' own subjective reports.Conclusions Neurometer CPT is effective for evaluating and comparing preoperative and postoperative facial sensory status and evaluating the sensory recovery period in facial bone fracture patients.
Keywords: Zygomatic fractures; Orbital fractures; Hypesthesia